PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII7 SMP NEGERI 25 PEKANBARU - Madhavia, Putri; Heleni, Susda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This classroom action research is aimed at improving learning process and improving math achievement by implementing Cooperative Learning Model with structural Think Pair Square (TPS) Aproach. The research subjects are 40 heterogeneus academic ability level students of the VIII7 class of Junior High School 25 Pekanbaru in academic year of 2016/2017. The research consested of two cycles in which each cycle consisted of four phase, i,e: namely planning, implementing, observing, and reflecting. By the end of cycle, daily test was held. The data was collected by means of observation and daily test. The action success indicators were if there is learning process improvement and the increasing number of students passing Minimum Completeness Criteria (MCC) in daily test I and daily test II. The research shows that teachers and students participated actively in the learning process. Therefore it can be said improvement of learning process took place in every meeting. Furthermore, the number of students passing MCC on base score, daily test I (first cycle), daily test II (second cycle) were respectively 16 students (40%), 20 students (50%), and 28 students (70%). The percentage of MCC achievement also indicates the increase after the implementation, thus it can be said that the students math achievement also increase. Finally, the research also shows that cooperative learning model with structural Think Pair Square (TPS) approach can improve math achievement of VIII7 class of Junior High School 25 Pekanbaru.